Performance modelling, life cycle assessment, and life cycle cost analysis of natural rubber latex modified asphalt pavement - Suwarto, Fardzanela (2024)
Over the past years, emissions from road construction have significantly increased due to substantial road development. Furthermore, considering the significance of the decreasing oil reserves, both the road industry and researchers are exploring alternative modifiers for use in pavement production. Further research has been undertaken to investigate renewable modifiers and bio-binders as potential alternatives to synthetic additives in the manufacturing process of bitumen mixtures and modified binders. Therefore, asphalt mixture producers are gradually utilising alternative modifiers, such as natural rubber latex (NRL). Previous research has shown that the use of NRL provides a binder with lower phase angles and a higher complex modulus than the conventional binder. This can indicate an improved ability to increase the fatigue resistance and withstand the deformation of the asphalt binder. Furthermore, the incorporation of NRL into the asphalt mixture increases its stability and reduces the flow number compared to the base asphalt mixture. Additionally, the NRL-modified asphalt mixture provides higher resistance to the rutting phenomenon and increases fatigue life. However, despite the fact that NRL offers many benefits, there has not yet been information or studies to compare NRL with readily available polymers or to what extent it can substitute available polymers when compared to the same percentage of polymers. Therefore, it cannot be argued that NRL can replace commercial polymers such as styrene butadiene rubber (SBS) polymer as the most widely used polymers for bitumen modification. Furthermore, no research has been conducted to assess the feasibility of using NRL in asphalt mixtures that consider both environmental and economic factors during its life cycle in order to determine whether it is the most optimal solution for asphalt materials. Therefore, this research presents an extensive assessment of an asphalt mixture using a multidisciplinary study that examines the mechanical performance of NRL. These emissions contribute to the carbon footprint using a life cycle assessment (LCA) and economic viability using a life cycle cost analysis (LCCA). Three binder mixtures consisting of Virgin binder, NRL, and SBS mixtures with percentages of 5% polymer by the weight of the binder are investigated in terms of their rheological properties. Following that, an asphalt mixture test is conducted on a stone-mastic asphalt mixture with a 6.6% asphalt content. The asphalt mixture with three different asphalt binders were then subjected to the asphalt mixture performance test. The asphalt binder test indicates that the NRL binder offers a higher elastic response, stiffness, and resistance to rutting than the Virgin binder, while it is still lower than the SBS binder. The tests on the mixture showed that adding NRL made it stronger in tensile strength, stiffness modulus, resistance to deformation, and fatigue life compared to a regular asphalt mixture. However, the NRL mixture had slightly lower values than the SBS mixture. The performance model was carried out using the (mechanistic empirical pavement design) MEPDG-based software, the AASHTOWare, to predict pavement distress on stone mastic asphalt (SMA) pavements in two case studies: the United Kingdom and Thailand. The laboratory test result was fitted as a material-specific laboratory-derived parameter to quantify permanent deformation and fatigue cracking on a monthly basis for the 60-year analysis period. Subsequently, using distress versus time charts, a pavement maintenance strategy was scheduled for each pavement section. The results show that this method is considered adequate and can be used to predict the permanent deformation and bottom-up cracking of asphalt pavements. Overall, in Thailand, all asphalt mixture combinations exhibited greater rutting than in the case study from the UK as a result of the higher temperature. Both case studies demonstrate that NRL has a lower degree of rutting than Virgin. However, NRL still has a higher level of rutting compared to SBS over 20 years. The prediction of bottom-up cracking indicates that NRL and SBS have similar performance, while Virgin SMA reached substantially higher bottom-up cracking over 20 years. In the UK, pavement maintenance analysis utilising mill and fill demonstrates that NRL and SBS SMA require half the maintenance frequency compared to Virgin, owing to their higher performance. However, NRL will require maintenance earlier than SBS. The model prediction can be applied to optimise the structure of the pavement design. This was achieved by optimising the thickness of the surface layer to obtain equivalent performance for the three proposed asphalt mixtures, with NRL SMA used as a point of reference. In this study, the optimised result design was designated as Scenario 2. The results determined that Virgin SMA requires a greater thickness to achieve the same level of performance as NRL SMA, whereas SBS has the potential to decrease the required thickness The environmental impact was assessed using a full-cycle LCA, which incorporated pavement performance modelling and maintenance analysis. global warming potential (GWP), which is considered one of the most significant indicators, was calculated using the Simapro software to measure the environmental impact on a 1 km road with a 7m wide lane of pavement constructed using the studied asphalt mixture. The GWP impact shows that despite the increased impact during the raw material production and asphalt mixture phases, NRL has the lowest total GWP impact across all proposed alternatives in both case scenarios and case studies. The result was attributed to less frequent maintenance performed in comparison to Virgin, as well as a lower GWP value in the production of basic materials in contrast to SBS. Furthermore, it was found that among all life cycle phases considered, the maintenance phase contributes the greatest percentage to the GWP, followed by raw material and asphalt mixing phases. Additionally, in the absence of sustainable material alternatives, implementing strategies to optimise pavement design and maintenance is a feasible option to minimise the environmental footprint. The LCCA was performed using the Realcost software to measure both the costs incurred by the agency and the costs borne by users of the work zone (WZ) when employing NRL-modified binder pavement. The analysis considered both the initial construction costs and the future costs associated with different alternatives in order to identify the alternatives that offer the highest economic advantage. The outcome of a pavement performance and maintenance analysis was integrated into the analysis to calculate future costs associated with the maintenance work during the full cycle of pavement life. A 4% discount rate was applied to adjust the initial construction and future costs to the present value. Subsequently, the remaining service life at the end of the analysis period was accounted for as the last maintenance activity benefit and deducted from the total NPV. The study found that in Scenario 1, NRL had the lowest agency cost in the UK, and SBS had the lowest in Thailand. SBS costs outperform NRL in Thailand due to its higher remaining service life (RSL). On the other hand, NRL incurred the lowest agency cost in both case studies for Scenario 2. Regarding user cost, NRL provided the least NPV in Scenario 2. At the same time, in Scenario 2, optimisation resulted in a similar NPV across all alternatives due to the fact that all mixtures exhibit identical durability. In addition, the total NPV result indicates that the NRL segment has the lowest overall NPV in both case studies and scenarios, followed by the SBS and Virgin segments.